Striatal Beta Oscillation and Neuronal Activity in the Primate Caudate Nucleus Differentially Represent Valence and Arousal Under Approach-Avoidance Conflict - Amemori, Ken-ichi; Amemori, Satoko; Gibson, Daniel J.; Graybiel, Ann M. (Frontiers in Neuroscience, 2020)
An approach-avoidance (Ap-Av) conflict arises when an individual has to decide whether to accept or reject a compound offer that has features indicating both reward and punishment. During value judgments of likes and dislikes, arousal responses simultaneously emerge and influence reaction times and the frequency of behavioral errors. In Ap-Av decision-making, reward and punishment differentially influence valence and arousal, allowing us to dissociate their neural processing. The primate caudate nucleus (CN) has been implicated in affective judgment, but it is still unclear how neural responses in the CN represent decision-related variables underlying choice. To address this issue, we recorded spikes and local field potentials (LFPs) from the CN while macaque monkeys performed an Ap-Av decision-making task. We analyzed 450 neuronal units and 667 beta oscillatory activities recorded during the performance of the task. To examine how these activities represented valence, we focused on beta-band responses and unit activities that encoded the chosen value (ChV) of the compound offer as derived from an econometric model. Unit activities exhibited either positive (65.0% = 26/40) or negative (35.0% = 14/40) correlations with the ChV, whereas beta responses exhibited almost exclusively positive correlations with the ChV (98.4% = 62/63). We examined arousal representation by focusing on beta responses and unit activities that encoded the frequency of omission errors (FOE), which were negatively correlated with arousal. The unit activities were either positively (65.3% = 17/26) or negatively (34.6% = 9/26) correlated with the FOE, whereas the beta responses were almost entirely positively correlated with the FOE (95.8% = 23/24). We found that the temporal onset of the beta-band responses occurred sequentially across conditions: first, the negative-value, then low-arousal, and finally, high-value conditions. These findings suggest the distinctive roles of CN beta oscillations that were sequentially activated for the valence and arousal conditions. By identifying dissociable groups of CN beta-band activity responding in relation to valence and arousal, we demonstrate that the beta responses mainly exhibited selective activation for the high-valence and low-arousal conditions, whereas the unit activities simultaneously recorded in the same experiments responded to chosen value and other features of decision-making under approach-avoidance conflict.